Transcatheter aortic valve replacement explant various techniques - Brescia, Alexander A.; Kachroo, Puja; Kaneko, Tsuyoshi (Annals of Cardiothoracic Surgery; Vol 14, No 2 (March 31, 2025): TAVR Explant, 2025)
Surgical aortic valve replacement (SAVR) has long been the gold standard for treating significant aortic valve dysfunction. Since the introduction of transcatheter aortic valve replacement (TAVR) in 2011, the number of TAVRs has grown rapidly, surpassing SAVR volumes by 2018 and now accounting for approximately 80% of all aortic valve replacements (AVRs) performed in the United States. In conjunction with the rapid expansion of TAVR, the number of TAVR valves requiring surgical explantation (TAVR-explant) has also increased due to procedure-related failure, endocarditis, structural valve degeneration with unfavorable anatomy for redo-TAVR, paravalvular leak, delayed migration, or prosthesis-patient mismatch. Often involving concomitant cardiac surgery, TAVR-explant has been associated with higher operative mortality than redo-SAVR. TAVR-explant is currently the fastest-growing cardiac procedure in the United States and is expected to continue growing, especially as TAVR is increasingly used for lower surgical risk and younger patients. Accordingly, describing and disseminating a standardized set of technical principles for performing TAVR-explant is essential for preparing all cardiac surgeons to appropriately treat these patients. TAVR-explant requires a comprehensive preoperative clinical and cross-sectional imaging assessment to plan an effective operation, including cannulation, aortotomy, explantation, and implantation strategies. Particular considerations for self-expanding and balloon-expandable TAVR valves are important for guiding the operation and optimizing outcomes. Special considerations, such as the need for concomitant aortic, coronary, or mitral valve surgery and the presence of snorkel coronary artery stents adjacent to the TAVR valve, must be considered and addressed at the time of TAVR-explant surgery. Currently, TAVR-explant confers a high operative mortality and is performed at very low volumes per surgeon. As this operation becomes increasingly common, it will become essential for all cardiac surgeons to understand and implement the operation’s various techniques to optimize patient outcomes.